Vigor and damage of soybean seeds estimated by sequential Bayesian techniques in the tetrazolium test (Acta Scientiarum. Agronomy, 2025)
Soybean is an oilseed of great relevance to Brazil because it is one of the main crops produced in the country. The success of this crop depends on several factors, the main one being seed quality. The tetrazolium test has been used for quality control because in addition to evaluating the viability of germination and the vigor of the seed lots, it facilitates classification of the types of damage. Thus, the use of sequential sampling, which takes into account the immediate evaluation of each seed, may facilitate an earlier decision on viability and vigor without the need to evaluate all seeds as in the classic test as a formality of the method. In addition, the estimates obtained through Bayesian techniques can be improved by including prior information. The objective of this study was to study the application of Bayesian sequential tests to estimate the proportion of vigor in lots (binomial modeling) and the proportion of damage per category in soybean seeds (multinomial modeling) through the tetrazolium test. In each case, conjugate priors were used, and the parameters were elicited. It can be concluded that the four approaches, frequentist, Bayesian, sequential, and Bayesian sequential, were efficient for estimation of and decision-making about the parameters, with a reduction in the sample size. Moisture damage was present in 20.17% of the soybean seeds evaluated, damage by stink bugs in 3.50%, and mechanical damage, in the case of manual harvesting, in only 1.92%. In addition, 1.00% of seeds presented more than two types of damage.